The psychology of flavour - Stevenson, Richard J. (Oxford University Press, 2009)
Flavour is arguably the most fascinating aspect of eating and drinking. It utilises a complex variety of senses and processes that incredibly work together to generate a unified, and hopefully pleasurable, experience. This text explores and describes what we know about the psychology and biology of flavour.